Improving reliability calculation with augmented binary decision diagrams - Herrmann, Johannes u (IEEE Computer Society, 2010)
The Augmented Ordered Binary Decision Diagram (OBDD-A) has been shown to be extremely efficient for reliability calculations, especially when combined with the Boundary Set method of partition representation. The existing OBDD-A follows the Boundary Set method closely, requiring the calculation of partition numbers large enough to exceed the capacity of native storage types in languages such as C++. By omitting the use of partition numbers the execution speed of the algorithm is increased, while the low memory usage of an OBDD-A is maintained. We compare the new OBDD-A to the existing version on a number of networks, showing that processing time for large networks increases significantly.